Influence of the Solid Oxide Electrolysis Component Characteristics on the Electrochemical Performance of SOE Cells. (2nd June 2015) - Tamm, Kadi; Kukk, Freddy; Salvan, Laur Kristjan; Kanarbik, Rait; Möller, Priit; Nurk, Gunnar; Lust, Enn
Abstract : Electrochemical behavior of four solid oxide electrolysis cells (SOEC) cells with different cathode microstructures, chemical compositions and electrolyte thicknesses have been tested using cyclic voltammetry, impedance spectroscopy and other electrochemical methods. Influence of cathode composition and thickness as well as electrolyte thickness, temperature and gas composition in cathode compartment on the SOE parameters has been demonstrated. It was shown that the polarization resistance ( R P ) decreases with the replacement of Ni-YSZ to Ni-GDC. The lowest R P has been measured for single cell consisting supportive ScSZ electrolyte and thin Ni-GDC cathode layer.